Perlindungan Hukum Terhadap Hak-Hak Narapidana Di Lembaga Pemasyarakatan Kelas IIB Ngawi - Kantrey Sugiarto; Kurniawan Bagus Wiacaksono; Sumiati Sumiati; Sangrila Puspita Dewi (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2021)
Abstract— Prisoners who are placed in prison are sometimes considered to have no rights whatsoever. They are sometimes treated inhumanely because they are considered to have committed a mistake or a crime so that their actions must be repaid in prison. The method used in this paper is normative juridical, which is research that is focused on studying the norms or norms in positive law which are then used as legal material to conduct research in Class II B Ngawi Prison regarding the rights of prisoners there. The efforts made by Ngawi Prison in the context of fulfilling the rights of prisoners have referred to the provisions of the applicable laws and regulations. In an effort to fulfill the rights of prisoners, it was found that there were obstacles faced due to the overcapacity of the inhabitants of the Ngawi Prison. With the results of this research, the main potential in the future is that it can be used as reference material for future prisoners, as a reference for further research with the development of the theme of over capacity, and as a bridge of information to overcome the gap between life in prison and the outside world. Keywords—: Prisoners; Rights; Protection.